2013
DOI: 10.2478/acss-2013-0003
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the Two-Hemisphere Model-Driven Approach for Generation of the UML Class Diagram

Abstract: In this paper an ability to apply the two-hemisphere model-driven approach for creation of the UML class diagram is discussed and the way to avoid the limitations of the approach is offered. The result of the proposed improvement of the twohemisphere model-driven approach is the increased number of elements of the UML class diagram available for automatic generation and several statements for semi-automatic transformation of business process diagram and the concept diagram into software components. As a result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Regarding the evaluation of the FOM-based approaches, only [61] presents evaluation results based on a controlled experiment (but the authors do not focus on the assessment of method effectiveness and efficiency). Regarding the evaluation of the POM-based approaches, three papers [21,23,47] report case-study based evaluation, while the results of controlled experiments are reported in [28,34,7,19]. The most complete evaluation results of an MDSDM approach, which are based on the experiment conducted with a significant number of database practitioners, are presented in [19,20] (average model completeness and precision are over 80%).…”
Section: Related Workmentioning
confidence: 99%
“…Regarding the evaluation of the FOM-based approaches, only [61] presents evaluation results based on a controlled experiment (but the authors do not focus on the assessment of method effectiveness and efficiency). Regarding the evaluation of the POM-based approaches, three papers [21,23,47] report case-study based evaluation, while the results of controlled experiments are reported in [28,34,7,19]. The most complete evaluation results of an MDSDM approach, which are based on the experiment conducted with a significant number of database practitioners, are presented in [19,20] (average model completeness and precision are over 80%).…”
Section: Related Workmentioning
confidence: 99%
“…This is achieved by using Abstract Syntax Tree Method. Nikiforova [18] explored the model driven approach for transforming hemisphere to UML class diagram. Abdullah [19] presented a method for model transformation from UML class diagram to source code.…”
Section: Related Workmentioning
confidence: 99%
“…Oasis considered CIM to include business model and requirement model [7], Laforcade took CIM as a business model [8], Kirikova thought CIM as an information processing model [4], Gherbi thought CIM as a requirement model, and PIM as analysis and design models [9], Luciana considered PIM as a business model [10], Nikiforova divided PIM into a business layer and an application layer [11]. In addition, models and corresponding representations are also inconsistent, as Yamin used class diagram to describe PIM [5], and Sharifi used activity diagram to model business [12].…”
Section: A Brief Overview Of Related Researchesmentioning
confidence: 99%